The impact of probiotic supplementation on gastric motility and nutrient absorption in elderly patients with Gastrointestinal disorders - Pingting Gong; Xuehong Tang (BMC Gastroenterology)
Abstract Background Gastrointestinal disorders (GIDs) in the elderly often lead to impaired gastric motility and nutrient absorption, exacerbating malnutrition. Probiotics, particularly Lactobacillus rhamnosus GG (LGG), may enhance gastric motility and nutrient absorption. This study evaluates the impact of LGG supplementation on gastric motility and nutrient absorption in elderly patients with GIDs. Methods A retrospective analysis was conducted on 231 elderly patients with GIDs, divided into a probiotic supplementation (PS) group (n = 110) and a NPS group (n = 121). The PS group received LGG (1 × 1010 CFU, twice daily) for at least 7 days. Baseline and post-treatment measurements included gastric motility via ultrasonography, gastrointestinal hormone levels using radioimmunoassay, and nutrient absorption markers through ELISA and calorimetry. Results Post-treatment, the PS group exhibited significantly improved gastric motility, with increased antral contraction amplitude (58.65 mm vs. 56.53 mm; P = 0.004), frequency (4.06 vs. 3.81 times/min; P = 0.009), and reduced gastric half-emptying time (28.15 min vs. 29.77 min; P = 0.007). Hormone analyses showed elevated motilin and neuropeptide Y levels and decreased vasoactive intestinal peptide levels in the PS group (P < 0.05). Nutrient absorption markers indicated decreased stool fat, protein, and carbohydrate content, enhanced intestinal permeability, increased weight and digestibility of energy, fat, and protein in the PS group (P < 0.05). Conclusion PS with LGG significantly enhances gastric motility and nutrient absorption in elderly patients with GIDs, indicating potential therapeutic benefits for addressing digestive dysfunction and malnutrition in this demographic.